Poor sleep quality and its determinants among stroke survivors in Northwest Ethiopia - Gashaw Walle Ayehu; Assefa Agegnehu Teshome; Nega Dagnew Baye; Getachew Yideg Yitbarek; Abraham Tsedalu Amare; Aragaw Tesfaw; Sintayehu Asnakew; Daniel Atlaw (Scientific Reports)
Abstract Sleep disorders are highly prevalent and linked bidirectionally to stroke as risk factors for stroke to worsen the outcomes. To date, most of the studies on post-stroke sleep were conducted in Western countries. Quality of sleep among stroke patients is masked by other physical and medical complications and limited attention is given in Ethiopia. To address this gap the current study aims to estimate the incidence of poor sleep quality and its determinants among stroke survivors in Northwest Ethiopia. A prospective cohort study was conducted in three public referral hospitals from June 2022 to December 2022. The study included 403 stroke survivors at the three-month follow-up. We conducted analyses of bivariable and multivariable logistic regression to look into the relationship between the outcome and the explanatory variables. Statistics were given as odds ratios and 95% confidence intervals, with a significance level of p < 0.05. The overall incidence of poor sleep quality was 50.1%, with a mean Global Sleep Quality (GSQ score) of 5.15 (SD ± 0.16). According to Pittsburgh Sleep Quality Index (PSQI) data, the mean sleep hour was 6.15. History of alcohol consumption, complications during admission, and time between the onset of symptoms and hospital arrival were predictors of sleep quality. Sleep quality was observed in half of stroke survivors. The study’s findings point to the significance of screening for sleep quality following a stroke and further research is needed including admitted and non-admitted stroke patients.